Functional Measures in Non-COPD Chronic Respiratory Diseases: A Systematic Review - Zamboti, Camile Ludovico [UNESP]; Pimpão, Heloise Angélico [UNESP]; Bertin, Larissa Dragonetti; Krinski, Gabriela Garcia; Garcia, Tathielle [UNESP]; dos Santos Filho, Sandro Laerth Souza; Cavalheri, Vinicius; Pitta, Fabio; Camillo, Carlos Augusto [UNESP] (MDPI, 2024)
Background/Objectives: The extensive range of instruments designed for evaluating functional performance (FP) in chronic respiratory diseases (CRD) other than chronic obstructive pulmonary disease (COPD) presents a challenge in selecting the most appropriate one. Therefore, this systematic review aimed to summarise FP instruments, their measurement properties, their minimum clinically important differences, and their associations with CRD course-related events or prognosis in non-COPD CRD. Methods: Studies employing patient-reported or performance-based instruments to assess FP in non-COPD CRD were systematically identified in the PubMed, PEDro, Embase, and Cochrane Library databases. COPD-exclusive studies or those solely reporting exercise capacity tests were excluded. Examination focused on measurement properties and associations with CRD course-related events or prognosis. The risk of bias was evaluated using the COSMIN, Downs and Black, and PEDro checklists based on the study design. Results: A total of 216 studies across seven CRD categories [asthma, bronchiectasis, cystic fibrosis, interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), pre-/post-lung-transplantation] from various study types were included. Thirty-three instruments were identified, with the SF-36 questionnaire's physical function domain being the most commonly used patient-reported tool. The 1 min sit-to-stand test was the most extensively studied performance-based measure, with its measurement properties frequently reported in non-COPD CRD studies. Associations with events were infrequently documented, primarily in ILD and PAH studies related to mortality. Conclusions: Despite the prevalent use of FP instruments, limited information exists concerning their measurement properties and clinical implications. This review furnishes a concise summary of available evidence, aiding informed clinical decisions when selecting FP tools for non-COPD CRD.